2017
DOI: 10.1002/pi.5467
|View full text |Cite
|
Sign up to set email alerts
|

Chitosan adsorbents for dye removal: a review

Abstract: One of the most important decontamination techniques is considered to be adsorption. It is fast, simple, low cost with many opportunities to modify the initial materials after appropriate synthesis routes etc. Numerous adsorbent materials have been prepared in the last few years having as the ultimate scope to remove some pollutants especially from contaminated waters (effluents originating from industry). But the composition of each type of effluent varies. Dyes are some major components of industrial wastewa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
66
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 165 publications
(70 citation statements)
references
References 103 publications
3
66
0
1
Order By: Relevance
“…In the past two decades, these materials used as biosorbents have received much attention in water and wastewater treatment, mainly for metal chelation and dye removal Crini 2015;Kos 2016;Muya et al 2016;Kanmani et al 2017;Kyzas et al 2017;Nechita 2017;de Andrade et al 2018;Desbrières and Guibal 2018;El Halah et al 2018;Pakdel and Peighambardoust 2018;Wilson and Tewari 2018). Indeed, chitosan has an extremely high affinity for metals and metalloids and for many classes of dyes, including direct, acid, mordant and reactive.…”
Section: Chitosan For Wastewater Treatmentmentioning
confidence: 99%
“…In the past two decades, these materials used as biosorbents have received much attention in water and wastewater treatment, mainly for metal chelation and dye removal Crini 2015;Kos 2016;Muya et al 2016;Kanmani et al 2017;Kyzas et al 2017;Nechita 2017;de Andrade et al 2018;Desbrières and Guibal 2018;El Halah et al 2018;Pakdel and Peighambardoust 2018;Wilson and Tewari 2018). Indeed, chitosan has an extremely high affinity for metals and metalloids and for many classes of dyes, including direct, acid, mordant and reactive.…”
Section: Chitosan For Wastewater Treatmentmentioning
confidence: 99%
“…Indeed, chitosan has an extremely high affinity for metals and metalloids and for many classes of dyes, including direct, acid, mordant and reactive. In their comprehensive reviews, Crini (2015), Yong et al 2015, Kyzas et al (2017), Wang and Zhuang (2017), Desbrières andGuibal (2018), El Halah et al (2018) and Pakdel and Peighambardoust (2018) recently indicated that biosorption onto chitosan was a promising alternative to replace conventional adsorbents used for decolorization purposes, metal chelation or recovery, and organic removal. With nutraceuticals and cosmeceuticals, the water and wastewater treatment field seems to be the next market in the development of chitosan.…”
Section: Chitosan For Wastewater Treatmentmentioning
confidence: 99%
“…The reader is encouraged to refer to the original articles for information on experimental conditions. Crini (2015), Kyzas et al (2017), and Wang and Zhuang (2017) demonstrated that biosorption using non-conventional cross-linked chitosan hydrogels is an effective and economic method for water decolorization. These materials had an extremely high affinity for many classes of dyes commonly used in industry with outstanding biosorption capacities, in particular anionic dyes such as acid, reactive and direct dyes (Table 10.4).…”
Section: Biosorption Capacitymentioning
confidence: 99%
See 2 more Smart Citations